Synthesis and binding mode predictions of novel Siglec-7 ligands - Frank, Martin; Kuhfeldt, Elena; Cramer, Jonathan; Watzl, Carsten; Prescher, Horst (Journal of medicinal chemistry, 2023)
Siglec-7 regulates immune cell activity and is a promising target for immunomodulation. Here, we report the discovery of novel sialic acid derivatives binding to Siglec-7. Synthesis and affinity measurements are complemented by high-quality models of sialoside-Siglec-7 complexes based on molecular dynamics (MD) simulations on the microsecond time scale. We provide details for the predicted binding modes for the new ligands, e.g., that an extension of the carbon backbone leads to a different molecular interaction pattern with the receptor and the nearby water structure than found for known Siglec-7 ligands. Further on, we uncover some shortcomings of the GLYCAM06 and GAFF2 force fields when used for the simulation of sialoside-based glycomimetics. Our results open new opportunities for the rational design of Siglec-7 inhibitors. In addition, we provide strategies on how to use and visualize MD simulations to describe and investigate sialoside-Siglec complexes in general.